2018
DOI: 10.1002/acn3.564
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rituximab infusion protocol on the long‐term outcome in anti‐MuSK myasthenia gravis

Abstract: ObjectiveTo evaluate whether the clinical benefit and relapse rates in anti‐muscle‐specific kinase (MuSK) myasthenia gravis (MG) differ depending on the protocol of rituximab followed.MethodsThis retrospective multicentre study in patients with MuSK MG compared three rituximab protocols in terms of clinical status, relapse, changes in treatment, and adverse side effects. The primary effectiveness endpoint was clinical relapse requiring a further infusion of rituximab. Survival curves were estimated using Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…These studies have demonstrated 100% complete stable remission for the use of RTX in MuSK MG (125,174), while 56% of AChR patients experienced a relapse within an average of 36 months after treatment -a finding that was replicated in another similar independent study (125,167). Although MuSK MG patients respond very well to treatment with RTX, relapses do occur, and the relapse rate is dependent on the applied RTX treatment protocol (176). Consistent reductions in AChR autoantibody titers and clinical improvement were demonstrated in a cohort study involving six patients (174).…”
Section: B Cell Targeting Therapiesmentioning
confidence: 88%
“…These studies have demonstrated 100% complete stable remission for the use of RTX in MuSK MG (125,174), while 56% of AChR patients experienced a relapse within an average of 36 months after treatment -a finding that was replicated in another similar independent study (125,167). Although MuSK MG patients respond very well to treatment with RTX, relapses do occur, and the relapse rate is dependent on the applied RTX treatment protocol (176). Consistent reductions in AChR autoantibody titers and clinical improvement were demonstrated in a cohort study involving six patients (174).…”
Section: B Cell Targeting Therapiesmentioning
confidence: 88%
“…Rituximab is increasingly being used for MG treatment. In recent years, several studies showed that rituximab is efficient in reducing the number of exacerbations in patients with refractory MG [10][11][12][13]. In the AAN guidelines, it is recommended to use nonsteroid IST to reduce doses of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 patients (55.1%) were receiving non-steroid IST, of whom 11 were also receiving steroids. In all, 22 patients were treated using Protocol A, three using Protocol B, one using Protocol C and three using Protocol D, with a mean cumulative dose of 4.26 g [1][2][3][4][5][6][7][8][9][10]. The mean (range) follow-up after initiation of rituximab was 20.06 (0.17-68.93) months.…”
Section: Patientsmentioning
confidence: 99%
“…The discrepancy may be explained by differences in the definition of clinical relapse, corticosteroid tapering schedule and rituximab dosing regimen. 38…”
Section: Discussionmentioning
confidence: 99%